2006
DOI: 10.1136/gut.2005.068189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical activity and body size on survival after diagnosis with colorectal cancer

Abstract: Background: Physical inactivity and obesity increase the risk of colorectal cancer but little is known about whether they influence prognosis after diagnosis. Methods: Incident cases of colorectal cancer were identified among participants of the Melbourne Collaborative Cohort Study, a prospective cohort study of 41 528 Australians recruited from 1990 to 1994. Participants diagnosed with their first colorectal cancer between recruitment and 1 August 2002 were eligible. At the time of study entry, body measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
255
2
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(296 citation statements)
references
References 23 publications
22
255
2
15
Order By: Relevance
“…When we repeated our analysis restricting to stage III participants only, the significant association between weight loss and risk of mortality remained. PA Previous studies examining the relationship between being more physically active before diagnosis of CRC and survival found marginal (26) or no effects (8,9). However, studies of postdiagnosis PA have shown that being more physically active after diagnosis reduces the risk of allcause and disease-specific mortality in stages I to III CRC patients (7,8) and reduced risk of cancer recurrence and overall mortality in stage III CRC patients (7).…”
Section: Bmimentioning
confidence: 93%
“…When we repeated our analysis restricting to stage III participants only, the significant association between weight loss and risk of mortality remained. PA Previous studies examining the relationship between being more physically active before diagnosis of CRC and survival found marginal (26) or no effects (8,9). However, studies of postdiagnosis PA have shown that being more physically active after diagnosis reduces the risk of allcause and disease-specific mortality in stages I to III CRC patients (7,8) and reduced risk of cancer recurrence and overall mortality in stage III CRC patients (7).…”
Section: Bmimentioning
confidence: 93%
“…The evidence for obesity as a common risk factor in a number of human diseases, including colorectal cancer, has led to the hypothesis that the metabolic changes associated with chronic overeating and sedentary behaviors have a role in development of many pathologies 8 . The majority of epidemiologic studies support a role for obesity as a risk factor for colorectal adenomas [9][10][11][12][13][14][15][16][17][18] , cancers 12,[19][20][21][22][23][24][25][26][27][28][29][30] ; and colon cancer mortality 31,32 . These observations suggest a continuous action of the adverse effects of obesity along the adenoma to carcinoma continuum, starting early in colon tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown similar associations. 75,76 There are ongoing efforts to try to understand the mechanism of this survival effect, including the effects of exercise on the effectiveness of chemotherapy.…”
Section: 75mentioning
confidence: 99%